Knowledge regarding hazards and legislation of tobacco consumption among undergraduate students in Rajkot & Morbi Districts, Gujarat, India, 2016 - R. Matariya, Zalak; K. Namera, Harshida; Patel, Umed V. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco which is most common legally available hazardous substance, most of the new users in India’s is school children. For prevention and control of tobacco consumption, legislation lies at the very heart of any effective tobacco control programme. To assess knowledge regarding harmful effects and legislation of tobacco consumption among undergraduate students Methods: A cross sectional study carried out among 2000 students in 20 colleges of different streams of Rajkot and Morbi districts during February-March 2016 using self-administered questionnaire. Proportion of male: female was kept 3:1. Results: Knowledge regarding harmful effects of tobacco was present in 95.8% participants. 92.8% students believed that cancer is the harmful effect of tobacco consumption.77.3% students had knowledge that tobacco consumption is the leading cause of death in India. Television was the commonest source of knowledge of harmful effect of tobacco (71.9%). Only 15.9% students had knowledge regarding the penalty for violation of rules of tobacco consumption prohibition. Conclusion: Knowledge regarding harmful effects of tobacco consumption was present in majority of students but it had no association with tobacco consumption habit. Knowledge regarding legislation of tobacco consumption was poor among students.